Liquid chromatography and capillary electrophoresis in glycomic and glycoproteomic analysis - Molnarova, Katarina; Cokrtova, Katerina; Tomnikova, Alice; Krizek, Tomas; Kozlik, Petr (Monatshefte fur chemie, 2022)
Glycosylation is one of the most significant and abundant post-translational modifications in cells. Glycomic and glycoproteomic analyses involve the characterization of oligosaccharides (glycans) conjugated to proteins. Glycomic and glycoproteomic analysis is highly challenging because of the large diversity of structures, low abundance, site-specific heterogeneity, and poor ionization efficiency of glycans and glycopeptides in mass spectrometry (MS). MS is a key tool for characterization of glycans and glycopeptides. However, MS alone does not always provide full structural and quantitative information for many reasons, and thus MS is combined with some separation technique. This review focuses on the role of separation techniques used in glycomic and glycoproteomic analyses, liquid chromatography and capillary electrophoresis. The most important separation conditions and results are presented and discussed.
Keywords: Glycopeptide separation; Capillary zone electrophoresis; Glycan separation; High-pressure liquid chromatography; Proteomics